The importance of relational characteristics: a person-centered approach - Knight, Caroline; McLarnon, Matthew; Wenzel, Ramon; Parker, Sharon (SAGE, 2022)
Adopting a person-centred approach, we integrate the job demands-control-support model with relational work design theory to investigate employee work design profiles involving autonomy, workload, social support and prosocial characteristics (representing the combined influence of task significance and beneficiary contact). For a sample of Australian not-for-profit employees (N = 2421), we identified four work design profiles: ‘active connected’, ‘passive disconnected’, ‘high strain disconnected’ and ‘controlled disconnected’. The most favourable profile, active connected, demonstrated the highest vigour and social worth, and was predicted by people being in higher managerial positions and having permanent employment contracts. The high strain disconnected and controlled disconnected profiles were associated with greater psychological exhaustion. Longer working hours predicted membership of the high strain disconnected profile.